INFLAMMATORY MECHANISMS INVOLVED IN TENDON OVERUSE: RECENT INSIGHTS. Issue 9 (10th May 2013) - Scott, Alex; Behzad, Hayedeh
Abstract : This presentation will synthesise and review recent findings from our laboratory and others' on inflammatory mechanisms involved in tendon overuse injuries. Tendinopathy is a state of chronic tendon thickening and pain, usually as a result of overuse. Recent work has shown that repetitive loading of human tendon-derived cells leads to upregulation of TAC1, the mRNA encoding for Substance P1 —a pro-inflammatory neuropeptide which is known to contribute to tendon pain.2 In addition, previous work has found that mast cells are present in greater numbers in chronically overused tendon, 3 and that they degranulate in response to SP, releasing substances that directly influence human tenocyte collagen remodelling. Thus, both SP and one of its main targets—the mast cell—are over-represented in tendinopathic tissue. Mast cells have a high affinity for human tenocytes, forming elaborate inter-cellular junctions, and releasing substances which substantially influence tenocyte behaviour that could have relevance for improving outcomes following injury or overuse. For example, inhibiting mast cells results in a reduction of TGF-beta-related genes (related to scarring) and reduces the amount of tendon thickening following injury.4 Additionally, mast cells induce a large increase in COX-2 expression by human tenocytes. It is possible that a clinical strategy which incorporates inhibitors of mast cells could improve on outcomes with standard treatment.5